2012
DOI: 10.1209/0295-5075/97/65002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of magnetic-field gradients and boundaries on double-layer formation in capacitively coupled plasmas

Abstract: The axial position of a magnetic field gradient has been varied for capacitive discharges in the linear plasma device VINETA. For low magnetic fields (B ≤ O(10 mT)), double layers have been observed to form predominantly at the interface between the source and the plasma chamber. In particular, double layer position is independent of the position of the magnetic field gradient. However, shifting the axial location of the magnetic field gradient leads to a global change of the plasma potential and the strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…Numerical simulation also suggests the formation of current free double layer to be predominantly controlled by the increased ion loss in the diverging magnetic field region [29]. On the other hand, in the experiment of [22] locations of geometric expansion and maximum of magnetic field gradient are both varied and it is shown that stronger double layer is observed only when both these expansion points coincide. Therefore, the role of magnetic expansion with respect to geometric expansion is not yet fully understood.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Numerical simulation also suggests the formation of current free double layer to be predominantly controlled by the increased ion loss in the diverging magnetic field region [29]. On the other hand, in the experiment of [22] locations of geometric expansion and maximum of magnetic field gradient are both varied and it is shown that stronger double layer is observed only when both these expansion points coincide. Therefore, the role of magnetic expansion with respect to geometric expansion is not yet fully understood.…”
Section: Introductionmentioning
confidence: 83%
“…Various aspects of the plasma double layers have been investigated thoroughly during the last three decadesexperimentally [9,[15][16][17][18][19][20][21][22][23][24][25], theoretically [26,27] as well as in simulation [28][29][30]. Of the different types of plasmas that produce double layer potential structure, the one that has gained tremendous interest amongst many researchers [13,18,19,21,22] is the expanding helicon plasma where plasma is produced by helicon discharge in a source chamber and it is diffused to a diffusion chamber of larger diameter in an expanding magnetic configuration. In 2003, Charles et al [16] first reported double layer formation in such a device.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have directly addressed how the location of the geometric expansion relative to the magnetic field would effect the creation of the axial potential structure known to accelerate a supersonic ion beam or the formation of the high density conics downstream. To our knowledge, only two studies have reported comparisons of the axial characteristics of low-pressure expanding plasmas between cases in which the geometric expansion is and is not colocated with the diverging magnetic field [25,26]. The study by Schröder et al used the linear plasma device VINETA to assess the creation and position of double layer potential structures under different magnetic field and geometric conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive measurements [1][2][3][4][5][6][7] and analysis [8][9][10][11] of beam formation in current-free double layers (CFDLs) have been performed since the first beam observations in inductively coupled helicon plasmas. [12][13][14] Such beams are typically observed a short distance after the source plasma has flowed into an expansion chamber downstream from the source.…”
Section: Introductionmentioning
confidence: 99%